"A sweaty business" - Middle-class cooking during the 18th century (KULT_online, 2014)
This booklet from the series "Kleine Schriften zur Aufklärung" published by the Lessing-Akademie Wolfenbüttel contains a collection of recipes for middle-class dishes taken from Eva König's cook book. The series' goal is to draw a detailed picture of the age of enlightenment and its historical development in order to understand and appreciate it further. Therefore, in this volume the editors provide knowledge about Eva König's life and the contemporary cooking methods of the middle-class during the age of enlightenment.